2016
DOI: 10.3329/ajmbr.v2i1.27569
|View full text |Cite
|
Sign up to set email alerts
|

Effects of saline water on health status of pregnant women in coastal regions of Bangladesh

Abstract: Drinking water from natural sources in coastal region of Bangladesh has been contaminated by varying degrees of salinity which have detrimental effects on the health. Pregnancy itself is a crucial time for women and the salinity increases its vulnerability regarding the raising of blood pressure. The study was conducted to evaluate the effect of saline water intake on the health status of pregnant women at Barguna and Patuakhali districts, Bangladesh. Sodium (Na) concentration in urine samples was analyzed and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Lack of access to clean water and sanitation is a major issue in the urban coastal area of Senegal (Thiam et al, 2017). About 20 million coastal inhabitants have been affected directly or indirectly by flood (Rony et al, 2016). This study conducted in a remote coastal area where flood, river erosion and tidal surges is common (Haque, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Lack of access to clean water and sanitation is a major issue in the urban coastal area of Senegal (Thiam et al, 2017). About 20 million coastal inhabitants have been affected directly or indirectly by flood (Rony et al, 2016). This study conducted in a remote coastal area where flood, river erosion and tidal surges is common (Haque, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The adverse impact of salinity intrusion on health goes through drinking water as the coastal people of Bangladesh use the natural source of drinking water and after the super cyclone-Aila in 2009 their major sources of drinking water had been contaminated by salinity (Rasheed, 2014;Kabir et al, 2016). About 20 million people in the coastal regions of Bangladesh who extensively depend on rivers, tube wells, and ponds for washing, bathing, and drinking water is affected by varying degrees of salinity (Rony et al, 2016). Khan et al (2011) found that generally the coastal people's average estimated sodium intake from drinking water ranged from 5 to 16 g/day in the dry season, compared with 0.6 to 1.2 g/day in the rainy season.…”
Section: Social Sciencementioning
confidence: 99%